Normal Calcium-Activated Anion Secretion in a Mouse Selectively Lacking TMEM16A in Intestinal Epithelium - Vega, Génesis; Guequén, Anita; Johansson, Malin E. V.; Arike, Liisa; Martínez-Abad, Beatriz; Nyström, Elisabeth E. L.; Scudieri, Paolo; Pedemonte, Nicoletta; Millar-Büchner, Pamela; Philp, Amber R.; Galietta, Luis J.; Hansson, Gunnar C.; et al. (Frontiers in Physiology, 2019)
Calcium-activated anion secretion is expected to ameliorate cystic fibrosis, a genetic disease that carries an anion secretory defect in exocrine tissues. Human patients and animal models of the disease that present a mild intestinal phenotype have been postulated to bear a compensatory calcium-activated anion secretion in the intestine. TMEM16A is calcium-activated anion channel whose presence in the intestinal epithelium is contradictory. We aim to test the functional expression of TMEM16A using animal models with Cftr and/or Tmem16a intestinal silencing. Expression of TMEM16A was studied in a wild type and intestinal Tmem16a knockout mice by mRNA-seq, mass-spectrometry, q-PCR, Western blotting and immunolocalization. Calcium-activated anion secretion was recorded in the ileum and proximal colon of these animals including intestinal Cftr knockout and double mutants with dual Tmem16a and Cftr intestinal ablation. Mucus homeostasis was studied by immune-analysis of Mucin-2 (Muc2) and survival curves were recorded. Tmem16a transcript was found in intestine. Nevertheless, protein was barely detected in colon samples. Electrophysiological measurements demonstrated that the intestinal deletion of Tmem16a did not change calcium-activated anion secretion induced by carbachol or ATP in ileum and proximal colon. Muc2 architecture was not altered by Tmem16a silencing as was observed when Cftr was deleted from mouse intestine. Tmem16a silencing neither affected animal survival nor modified the lethality observed in the intestinal Cftr-null mouse. Our results demonstrate that TMEM16A function in the murine intestine is not related to electrogenic ion transport and does not affect mucus homeostasis and survival of animals.